The Splenic Marginal Zone in Children Is Characterized by a Subpopulation of CD27-Negative, Lowly IGHV-Mutated B Cells - Kibler, Artur; Budeus, Bettina; Küppers, Ralf; Seifert, Marc (Frontiers in Immunology, 2022)
Young children and older adults suffer from enhanced susceptibility to infections with blood-borne pathogens. An essential step towards immunity is the establishment of a splenic marginal zone (sMZ), which is immature at below 2 years of age. At approximately 5 years of age, an adult level of protection is reached but wanes again in older adults. Although the infant sMZ is thought to contain mostly naïve B cells, memory B cells are recruited to and recirculate from the sMZ throughout life, and class-switched sMZ B cells dominate in older adults. For a better resolution of naïve versus memory B-cell subset accumulation in the sMZ, we performed a single cell-based gene expression analysis of (CD21highIgMhigh) sMZ B cells among five healthy donors (age 3 to 48 years) and validated the sMZ B-cell subset composition by flow cytometry of 147 spleen biopsies (age 0 to 82 years). We identified a major sMZ B-cell subpopulation, which is abundant at birth but decreases with age. These cells lack CD27 expression but carry a weak-to-intermediate memory B-cell signature. These CD27neg sMZ B cells are either IGHV-unmutated or carry only a few IGHV mutations early in life but show average memory B-cell IGHV mutation frequencies (>3%) in adults. The activation and proliferation potential of CD27neg sMZ B cells is significantly above that of non-sMZ B cells already in children. Our study suggests that the human sMZ B-cell pool changes with age, encompassing a major population of lowly Ig-mutated CD27neg but antigen-experienced B cells early in life.